Antimutagenic and anticarcinogenic effects of wheat bran in vivo - Pesarini, J. R.; Zaninetti, P. T.; Mauro, M. O. [UNESP]; Carreira, C. M.; Dichi, J. B.; Ribeiro, L. R. [UNESP]; Mantovani, M. S.; Oliveira, R. J. (Genetics and Molecular Research, 2013)
Previous studies in rodents treated with the pro-carcinogen 1,2-dimethylhydrazine suggested that the consumption of wheat bran protected against DNA damage in the colon and rectum. Based on this information, we evaluated wheat bran as a functional food in the prevention and treatment of colon cancer. We used the aberrant crypt focus assay to evaluate the anticarcinogenic potential of wheat bran (Triticum aestivum variety CD-104), the comet assay to evaluate its antigenotoxicity potential, and the micronucleus assay to evaluate its antimutagenic potential. The wheat bran gave good antimutagenic and anticarcinogenic responses; the DNA damage decreased from 90.30 to 26.37% and from 63.35 to 28.73%, respectively. However, the wheat bran did not significantly reduce genotoxicity. Further tests will be necessary, including tests in human beings, before this functional food can be recommended as an adjunct in the prevention and treatment of colon cancer. © FUNPEC-RP.
Keywords: Chemoprevention; Functional food; Triticum aestivum; Wheat bran; DNA; animal experiment; antineoplastic activity; apoptosis; cancer risk; cell cycle; cell proliferation; colon cancer; comet assay; controlled study; DNA damage; genotoxicity; in vivo study; male; micronucleus test; mouse; mutagenicity; nonhuman; wheat bran